2017
DOI: 10.1111/imcb.1019
|View full text |Cite
|
Sign up to set email alerts
|

Beta‐catenin promotes macrophage‐mediated acute inflammatory response after myocardial infarction

Abstract: Regulatory mechanisms for acute inflammatory responses post myocardial infarction (MI) have yet to be fully understood. In particular, the mechanisms by which cardiac macrophages modulate MI-induced myocardial inflammation remains unclear. In this study, using a mouse MI model, we showed that β-catenin-mediated signaling was activated in cardiac macrophages post-MI, especially in Ly-6C-positive proinflammatory macrophages. Using a RAW264.7-based β-catenin reporter cell line, we confirmed the presence of active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
(50 reference statements)
0
15
0
Order By: Relevance
“…Wnt-5a promotes the release of IL-1, IL-6, and IL-8 from monocytes, indicating that it has a pro-inflammatory effect 485 . β-catenin-mediated signals are activated in pro-inflammatory macrophages after MI, which is manifested by increased lymphocyte infiltration levels and increased expression of proinflammatory cytokines 486 . In addition, another study reported that the absence of Wnt inhibitory factor 1 (WIF1) causes increased inflammatory monocytes and severe adverse remodeling, while overexpression of WIF1 weakens the monocyte response and improves cardiac function 487 .…”
Section: Wnt/β-catenin Signaling Pathway In MImentioning
confidence: 99%
“…Wnt-5a promotes the release of IL-1, IL-6, and IL-8 from monocytes, indicating that it has a pro-inflammatory effect 485 . β-catenin-mediated signals are activated in pro-inflammatory macrophages after MI, which is manifested by increased lymphocyte infiltration levels and increased expression of proinflammatory cytokines 486 . In addition, another study reported that the absence of Wnt inhibitory factor 1 (WIF1) causes increased inflammatory monocytes and severe adverse remodeling, while overexpression of WIF1 weakens the monocyte response and improves cardiac function 487 .…”
Section: Wnt/β-catenin Signaling Pathway In MImentioning
confidence: 99%
“… 264 266 The β-catenin protein is a transcriptional coactivator in Wnt pathway, which has been found to be involved in a number of biological processes of tumor cells, including proliferation, 267 , 268 anti-apoptosis, 269 and infiltration transfer. 270 The Wnt/β-catenin pathway is activated when the Wnt ligands bind to the seven-transmembrane receptor Frizzled (FZD) and the low-density lipoprotein receptor-related protein 5 or 6 (LRP5/6). 271 The Wnt-FZD-LRP5/6 trimer complex recruits disheveled (DVL) and axin through the intracellular domains of FZD and LRP5/6, thereby inhibiting β-catenin phosphorylation and ensuring β-catenin stability.…”
Section: Signaling Pathways In Gastric Cancer and Therapeutic Implica...mentioning
confidence: 99%
“…Scholars found that the Wnt/β-catenin signaling was activated in cardiomyocytes located in the border region of the infarct [ 33 ]. In addition, this pathway was also activated in pro-inflammatory macrophages in the myocardial infarction area, manifested by increased levels of lymphocyte infiltration and increased expression of pro-inflammatory cytokines [ 34 ]. Another study found that loss of Wnt inhibitory factor 1 (WIF1) can lead to increased inflammatory monocytes and severe myocardial adverse remodeling, while overexpression of WIF1 impairs monocyte response and improves cardiac function [ 35 ].…”
Section: Methodsmentioning
confidence: 99%